E-Trip : Mobile Application of Map Integrated for Post-Disaster Relief Needs - J Jawahir; Dedy Prasetya Kristiadi; S Sutrisno (IJISTECH (International Journal of Information System and Technology), 2022)
Disasters have become a threat to every citizen in this country. The government is responsible for protecting residents by evacuating victims, repairing damaged roads and building infrastructure as well as distributing logistics through the National Disaster Management Agency or BNPB. The goal is to provide a safe life for citizens. After a disaster occurs, the government through BNPB must immediately respond to location information to save lives and help victims. So that information can be sent quickly from information sources and received by the government, a reliable geographic information system is needed. The function of this information system will be to provide top management support to make decisions. An Android-based integrated GIS will serve as a guide for post-earthquake, flood and landslide action services by building collaborations for victim data collection and road and bridge infrastructure with the National Disaster Management Agency, Community Health Centers and private and private hospitals. This development will apply the latest technologies such as Data Warehouse, Big Data, Data mining, machine learning, knowledge management, Decision Support Systems and so on that handle structured and unstructured data. The development of an information system will be built on a smartphone application by digging information on the location of Indonesia's earthquake victims from social media.